ANALISIS KUALITAS PRODUK DAN PERANCANGAN STRATEGI OPERASI ENGAN MENGINTEGRASIKAN ANALISIS SWOT KEDALAM MODIFIED FUZZY QFD PADA PRODUK KOPI ARABIKA LERENG GUNUNG ARJUNO - ERLAN ANGGRIANA, 041711223042 (2019)
All methods for measuring and analyzing quality is growing up, in this study using the QFD (Quality Function eployment) method. There are several additions that are integrated in the method, namely SWOT analysis and fuzzy logic theory. Then the method is named Integrated SWOT Analysis to Modified Fuzzy QFD. This research was conducted on measuring the quality and operational strategy of the Arabica coffee of Mount Arjuno, with population and sample collection at Kedai Kita Café, Surabaya. Then the final results of this study obtained 10 aspects of the internal and external conditions of Mount Arjuno Arabica coffee farming which must be considered and developed with each particular priority and 2 operational strategies that must be carried out, it is from the product strategy and process strategy.